ADOPTING CONCEPTS OF MOTIVATION IN STAKEHOLDER PARTICIPATION IN ELECTRONIC GOVERNANCE PROJECTS; AN ANALYTICAL REVIEW - JENNIFER, ADALETEY E; RAJU, VALIAPPAN; PHUNG, SIEW POH (International Journal of Psychosocial Rehabilitation, 2020)
The present study examined factors that motivate stakeholders’ involvement in electronic governance projects implemented especially in developing countries. This analytical review hopes to identify ways of inspiring citizens to participate in electronic governance projects implemented, so as to facilitate the success of these projects. The key concepts identified in this analysis contributed to areas where governments can focus on to influence their citizens’ involvement and engagement in new public initiatives. The relevant literatures identified suggested that most public sector institutions adopt electronic governance and implement its changes however little efforts are contributed to post implementation issues; such as enforcing and sustaining stakeholder participation. The present study attempts to identify the motivations or factors that inspires the citizen’s involvement as an approach to contribute to revenue improvement and ways of sustaining citizen involvement especially in developing countries.